Mediation between the Aggrieved Party and the Perpetrator as a Form of Conflict-Solving (Archives of Criminology, 2008)
The goal of this article is to characterise mediation as a form of conflict resolution between offenders and victims. The article provides the characteristics of the issue of conflict, indicating its different faces, types, and methods for resoltion. The author describes and characterises avoidance, competition, mitigation, cooperation, and negotiation as styles of reaction to conflict. Moving on to the main issue, Marzena Kruk describes consensual ways of solving disputes, including mediation as a form of restorative justice. The paper presents various concepts, including the theory of social stigma, social control, and reintegrative shaming, which have contributed to the growing importance of restorative justice in conflict resolution. The article also highlights figures pivotal to restorative justice, such as Nile Christie, who advocated that crimes should be resolved by those who are a party to them, believing that conflict should not be ‘appropriated’ by the state. The text also discusses the history of the development of mediation programmes since the mid-1970s worldwide and in Poland. The author analyses the number of cases submitted to mediation proceedings between 1999 and 2007 in Poland. In the conclusion of the text, Kruk points out the benefits of mediation for both the victim and the perpetrator and stresses the value of redress in conflict resolution.